Comparing post-operative resource consumption following transcatheter aortic valve implantation (TAVI) and conventional aortic valve replacement in the UK. (May 2014) - Awad, W.; Mathur, A.; Baldock, L.; Oliver, S.; Kennon, S.
Abstract Objective: To define the in-hospital and 6-month post-discharge resource use, following Transcatheter Aortic Valve Implantation (TAVI) and conventional Aortic Valve Replacement (AVR) surgery within a single UK hospital. Methods: A local service evaluation of patients undergoing TAVI or AVR between January 2011 and May 2012 captured data until 6-months post-procedure, collected from hospital records and via a General Practitioner questionnaire. The main end-points were mortality, time in ITU/HDU, hospital length of stay (LoS), discharge destination, re-admission, and post-discharge primary/secondary care resource use. Sub-group analyses were performed for AVR patients aged ≥80 (AVR ≥ 80) and with EuroSCORE of ≥10 (AVR ES ≥ 10) to allow more direct comparison with 'TAVI type' patients. Results: Results are given as means (standard deviation) for TAVI (n = 51), AVR (n = 188), AVR ≥ 80 (n = 48), and AVR ES ≥ 10 (n = 47), respectively, unless otherwise stated. Age in years was 83.0 (8.1), 71.2 (13.1), 84.1 (2.7), 79.4 (7.1); EuroSCORE was 24.7 (11.9), 8.1 (6.4), 12.0 (6.0), and 16.5 (6.6); post-operative LoS (days) was 11.5 (11.2), 10.9 (10.8), 14.3 (16.7), and 15.2 (17.7). For discharged patients, 0%, 7%, 13%, and 9% had unplanned cardiac-related re-admissions within 30-days of discharge. Time to first readmission was 74.6 (34.0), 35.0 (34.2), 20.8 (9.7), and 22.6 (14.3) days. Limitations: This was a single-center retrospective evaluation, not prospectively powered to confirm differences in outcomes. Conclusions: Despite TAVI being performed in an older, higher risk population, LoS was similar to AVR. Most strikingly there were no cardiac-related re-admissions within 30-days for TAVI and time to first re-admission was significantly longer. This evaluation suggests that TAVI is clinically appropriate and provides economic advantages in both the hospital and post-discharge setting in this high risk group. Many patients undergoing TAVI are considered unfit for surgery and, hence, TAVI offers a treatment that delivers similar results to traditional AVR without the high risk associated with surgery.